1969
DOI: 10.1139/v69-309
|View full text |Cite
|
Sign up to set email alerts
|

Neutral reactions involving oxygen and nitrogen

Abstract: Methods of production and detection of reactive species of oxygen and nitrogen are discussed briefly. Kinetic data for reactions of these species which have aeronomic interest are reviewed. New data, obtained during the past 4 years are critically compared, and recommendations made for "best" values where possible. An attempt is also made to delineate important areas where additional work is needed to meet the demands of atmospheric modelling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1970
1970
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…1 illustrates the papers that provide values of these components for both the Rx [25,40,44,[47][48][49][50] and R2 [19,32,51] expressions. The literature dictates that one specific value for these terms (k, m, E) does not match all of the experimental data.…”
Section: Ozone Kineticsmentioning
confidence: 99%
“…1 illustrates the papers that provide values of these components for both the Rx [25,40,44,[47][48][49][50] and R2 [19,32,51] expressions. The literature dictates that one specific value for these terms (k, m, E) does not match all of the experimental data.…”
Section: Ozone Kineticsmentioning
confidence: 99%
“…These catalysts form predominantly from the dissociation of methane, the photodissociation of water vapour, mainly above 60 km, and the destruction of molecular hydrogen. Monitoring of the ozone layer (Gribben, 1989) had revealed that the amount of stratospheric ozone predicted by the Chapman equations (Schiff, 1969) was far larger than that observed (Hunt, 1966). These additional cycles were still too slow to account for the observed concentrations of ozone (Crutzen, 1970), meaning that further cycles required identification.…”
Section: L Stratospheric Ozone Climatologymentioning
confidence: 99%
“…The homogeneous reaction k D (D) O + ~Z + M -~~+ M followed by the fast reaction (E) k , 0 + 0 ~~2 0 ~ might remove the atomic oxygen with similar, but not greater, speed to that of reaction (C) if almost all the oxygen present is in the molecular form, but the exact rate is uncertain (Schiff 1969).…”
Section: Hydrogen-free Systemmentioning
confidence: 99%